Roundtable About Social Property - Pásara, Luis H. (1973)
From the official announcement of the next generation of social property of means of production, there have been several attempts to define the objectives, characteristics, the scope and other aspects of vital importance for its implementation and development. The University of Pacífico, specially its Management Department, did not want to stay out of this enriching debate. For this purpose, it assembled in last November a roundtable to clarify two important aspects: the immediate antecedents and the mechanisms of implantation of social property in Peru.